Application of a modified Plastofrost apparatus to coal rheology - P. D. Duever; P. L. Silveston; P. J. Readyhough (Canadian Institute of Mining, Metallurgy and Petroleum, 1987)
"The Plastojrost apparatus, developed by Ritter and Juranek in the 1960s has been modified primarily, to automatic temperature control. A limited investigation of carboniferous and cretaceous coal samples showed that both coals undergo the same changes when coked in the Plastofrost unit. Dilatometer plastic range and total dilatation correlated well with the Piastofrost plastic range for the carboniferous Appalachian coal, but not for the cretaceous western Canadian coal. Work to elucidate the characteristics of some western Canadian coals using the Plastofrost is in progress. IntroductionCoke quality is critically affected by the properties of the plastic phase in the coal-to-coke transformation. Since these properties exist in a coke oven and are not measurable, they are approximated by standard laboratory tests, such as free swelling index, plastometry, and dilatometry. Of particular interest to us is the anomalous behaviour of western Canadian coals of cretaceous origin. By many predictive methods, these coals should not produce coherent cokes. When coked in pilot scale test ovens, in fact, they produce cokes of good stability. They typically make up 20% of Japanese coking coal blends and are also used in South Korea, Mexico, Brazil, and several European countries. This anomalous behaviour has been studied in our laboratory<8.9.1O). Plastic properties or rheological tests examine just the external ramifications of the coal-to-coke transformation. To understand the process, however, microscopic examination of the coal and coke seems to be needed. The Plastofrost unit has been shown to be a convenient means to this end."